Pengaruh Digital Banking terhadap Loyalitas Nasabah Bank Syariah - Raihansyah Azdi Bintang; Rafly Ramadhan Simanjuntak; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The advancement of information technology has propelled changes in banking services, particularly within the realm of Islamic banking. Digital banking represents a breakthrough that offers ease, rapidity, and effectiveness in transactions. This research intends to examine how digital banking impacts customer loyalty within Islamic financial institutions. The methodology applied involves a literature review, which encompasses an examination of various academic articles, books, and research materials concerning digital banking and customer loyalty. Findings indicate that high-quality digital banking services, user-friendliness, transaction security, and customer satisfaction positively influence customer loyalty. The enhanced digital services offered by Islamic banks correspond to an increased level of loyalty among customers utilizing their products and services. Keywords: Digital Banking, Customer Loyalty, Islamic Bank, Customer Satisfaction, Banking Technology